Turkey and Japan: the quest of modernism in the 19th century - Mansor Majdin, Mohamad Firdaus (Global Academic Excellence (M) Sdn Bhd, 2020)
This paper will deal with the process of modernization of two emerging Asian powers, namely Japan and Turkey, with particular reference to important elements of Japanese and Turkish pursuits of modernization at the expense of growing Western penetration into their countries. This will specifically deal with the Meiji Restoration and Tanzimat Reforms where process of modernization has taken place. Furthermore, there will be a discussion on the efforts of Turkish statesmen and Japanese statesmen in their attempts to modernize several aspects of vital institutions in Turkey and Japan as well as issues concerning the modernization encountered by the Japanese statesmen and Turkish counterparts in their countries. Sources for this analysis will be taken from studies of both Western writers and inside writers on modernization in Japan and Turkey. The ability of Japanese and Turkish statesmen to adopt and adapt foreign practices which infused with local circumstances suggest that they are capable of modernizing their respective countries by their own rights.